Variation in Time in Therapeutic Range (TTR) of Warfarin Use in Atrial Fibrillation Patients at Hospital X, Banten - Benny Setiawan; Chelseata Ria Rebeka Br Sitepu; Anastasia Pramitaningastuti (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2025)
Atrial fibrillation is the most common sustained cardiac arrhythmia in adults. Stroke, resulting from thromboembolism, is the most frequent and severe complication associated with atrial fibrillation, and its prevention is a primary therapeutic goal. Anticoagulant therapy is the cornerstone for stroke prevention, with warfarin being the most commonly used anticoagulant. However, warfarin therapy poses a significant risk of bleeding, necessitating regular and strict monitoring. The Time in Therapeutic Range (TTR) is a parameter used to assess the quality of warfarin therapy management, reflecting the percentage of time a patient's INR remains within the target therapeutic range of 2.0–3.0. To evaluate the variation of Time in Therapeutic Range (TTR) and its association with complications in atrial fibrillation patients receiving warfarin therapy. TTR was calculated using the Rosendaal interpolation method. The risk of bleeding complications was assessed using the HAS-BLED score, and stroke risk was evaluated using the CHA₂DS₂-VASc score. This retrospective observational study included 78 atrial fibrillation patients receiving warfarin, whose medical records were collected from January to June 2022. Data were presented in tables and charts and analyzed descriptively. The study found that only 15.38% (12 patients) achieved the target TTR (>70%), while 84.62% (66 patients) had suboptimal TTR levels. Most patients with low TTR scores had moderate to high HAS-BLED and CHA₂DS₂-VASc scores, indicating an increased risk of bleeding and stroke.